A bifunctional small molecular photocatalyst with a redox center and a Lewis acid site for one-pot tandem oxidation–acetalization. Issue 15 (13th July 2022) - Rao, Cai-Hui; Ma, Shuai; Cui, Jing-Wang; Jia, Meng-Ze; Yao, Xin-Rong; Zhang, Jie
Abstract : A bifunctional photocatalyst combining a redox center and a Lewis acid site has been developed for one-pot tandem oxidation–acetalization, which involves pyridinium-mediated molecular oxygen activation, as well as Lewis-acid promoted acetalization. Abstract : By combining the double identity of a redox center and a Lewis acid site of the pyridinium derivative, the first bifunctional small molecule photocatalyst has been developed for the one-pot tandem oxidation–acetalization reaction. A mechanism study reveals that pyridinium-mediated electron transfer and the photoactivation of molecular oxygen greatly facilitate the transformation of benzyl alcohols into the corresponding aldehydes, while the Lewis acid site of this bifunctional photocatalyst promotes a highly efficient acetalization reaction without any significant loss in activity after multiple reaction cycles, thus achieving the direct conversion of various alcohols into either cyclic or acyclic acetals in good yields under mild conditions without any additives.